2021
DOI: 10.1016/j.socscimed.2021.113794
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Social Determinants of Health into Modelling of COVID-19 and other Infectious Diseases: A Baseline Socio-economic Compartmental Model

Abstract: The role of socio-economic conditions has been largely implicit in mathematical epidemiological models. However, measures to address the current pandemic, specifically the relevant interventions proposing physical distancing, have highlighted how social determinants affect contagion and mortality dynamics of COVID-19. For the most part, these social determinants are not present in either policy discussions or in relevant epidemiological models. We argue for the importance of incorporating relevant social deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…In [5], an analysis model of diagnosis and treatment for the COVID-19 pandemic based on medical information fusion was discussed, in [6] a model of the COVID-19 epidemic and predicting its future situation in Ethiopia was studied and in [7] a fractional order COVID-19 model with real-life data application was analyzed. The COVID-19 epidemic and clinical risk factors of patients under an epidemiological Markov model were discussed in [8] and the incorporating social determinants of health into modeling of COVID-19 and other infectious diseases was illustrated in [9].…”
Section: Introductionmentioning
confidence: 99%
“…In [5], an analysis model of diagnosis and treatment for the COVID-19 pandemic based on medical information fusion was discussed, in [6] a model of the COVID-19 epidemic and predicting its future situation in Ethiopia was studied and in [7] a fractional order COVID-19 model with real-life data application was analyzed. The COVID-19 epidemic and clinical risk factors of patients under an epidemiological Markov model were discussed in [8] and the incorporating social determinants of health into modeling of COVID-19 and other infectious diseases was illustrated in [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent rapid review of COVID-19 studies examining infection, health service use, and health outcomes, found a minority of studies that had assessed outcomes according to social determinants of health [18]. Moreover, social determinants are rarely incorporated into mathematical modelling studies, which have achieved substantive importance in informing policy-makers about the impact of disease and interventions in the population over time [19,20]. Thus, these studies may mask the differential exposure and effects across social determinants that are driving systemic inequalities [21].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 – 11 ]. One of the focuses of relevant models is the estimation of the effects of NPIs on the rate of spread of the epidemic, captured by the reproduction number, which differs across countries [ 12 ] and this can be due to a number of social and economic conditions [ 13 , 14 ]. Hence, the effectiveness of the different policies depends on how the various measures reduce this parameter.…”
Section: Introductionmentioning
confidence: 99%